Exploring Islamic Values in a Bataknese Song “Onang-Onang": A Semantics Analysis - Dinda Suciana Rambe; Romadhonna Siregar; Rabiyatul Adawiyah Harahap (Sunan Kalijaga: International Journal of Islamic Civilization, 2025)
"Onang-onang" is a song that was part of key pagan rituals in the cultural practices of the Angkola and Mandailing tribes, practices which once conflicted with Islam. Despite this historical background, it is intriguing to learn that this song, to some extent, shares values rooted in Islam. Using semantic analysis, this research aims to explore how Islamic values are reflected in "Onang-onang." This qualitative study, conducted through detailed descriptive content analysis, examines how Islamic principles are incorporated into the song. The research found that the Islamic values embodied within "Onang-onang" can be classified into four categories: (1) divinity, through prayers and praise to God; (2) compassion, through parent-child relations; (3) wisdom, through expressions of gratitude; and (4) social solidarity. The lyrics also contain explicit Islamic expressions, such as bismillah and alhamdulillah. Furthermore, it is conveyed that figures such as Bolon, mora, kahanggi, anak boru, raja panusunan, raja torbing blok, naposo nauli bulung, and namora pule would have a blessed future if they were willing to learn from previous experiences.